Clinical Efficiency and Safety Outcomes of Virtual Care for Oncology Patients During the COVID-19 Pandemic. Issue 9 (September 2021) - Hsiehchen, David; Muquith, Maishara; Haque, Waqas; Espinoza, Magdalena; Yopp, Adam; Beg, Muhammad S.
Abstract : PURPOSE: Telehealth has been an integral response to the COVID-19 pandemic. However, no studies to date have examined the utility and safety of telehealth for oncology patients undergoing systemic treatments. Concerns of the adequacy of virtual patient assessments for oncology patients include the risk and high acuity of illness and complications while on treatment. METHODS: We assessed metrics related to clinical efficiency and treatment safety after propensity matching of newly referred patients starting systemic therapy where care was in large part replaced by telehealth between March and May 2020, and 206 newly referred patients from a similar time period in 2019 where all encounters were in-person visits. RESULTS: Patient-initiated telephone encounters that capture care or effort outside of visits, time to staging imaging, and time to therapy initiation were not significantly different between cohorts. Similarly, 3 month all-cause or cancer-specific emergency department presentations and hospitalizations, and treatment delays were not significantly different between cohorts. There were substantial savings in travel time with virtual care, with an average of 211.4 minutes saved per patient over a 3-month interval. CONCLUSION: Our results indicate that replacement of in-person care with virtual care in oncology does not lead to worse efficiency or outcomes. Given the increased barriers to patients seeking oncology care during the pandemic, our study indicates that telehealth efforts may be safely intensified. These findings also have implications for the continual use of virtual care in oncology beyond the pandemic.